"Perwalian" Dalam Perundang-Undangan Indonesia, Irak dan Syria - Baidowi, Ahmad (Musawa Jurnal Studi Gender dan Islam, 2004)
Within the Islamic marriage law, the issue of guardianship (wali) is quite important to discuss. There is no agreement on the "position" ofthe guardian within marriage in various madzhab. Furthermore, there are debates within the feminists on this very issue. Within numerous laws in different Muslim countries such as Indonesia and Iraq, the issue of guardianship has undergone some changes. This article attempts at exploring four laws on the guardianship in three Muslim countries: Indonesia, Iraq, and Syria.